Neopterin and Beta-2 Microglobulin Relations to Immunity and Inflammatory Status in Nonischemic Dilated Cardiomyopathy Patients - Wojciechowska, Celina; Wodniecki, Jan; Wojnicz, Romuald; Romuk, Ewa; Jacheć, Wojciech; Tomasik, Andrzej; Skrzep-Poloczek, Bronisława; Spinczyk, Beata; Nowalany-Kozielska, Ewa (Mediators of Inflammation, 2014)
Background. The aim of the study was to assess the relationships among serum neopterin (NPT), β2-microglobulin (β2-M) levels, clinical status, and endomyocardial biopsy results of dilated cardiomyopathy patients (DCM). Methods. Serum NPT and β-2 M were determined in 172 nonischaemic DCM patients who underwent right ventricular endomyocardial biopsy and 30 healthy subjects (ELISA test). The cryostat biopsy specimens were assessed using histology, immunohistology, and immunochemistry methods (HLA ABC, HLA DR expression, CD3 + lymphocytes, and macrophages counts). Results. The strong increase of HLA ABC or HLA DR expression was detected in 27.2% patients—group A—being low in 72.8% patients—group B. Neopterin level was increased in patients in group A compared to healthy controls 8.11 (4.50–12.57) versus 4.99 (2.66–8.28) nmol/L (P<0.05). β-2 microglobulin level was higher in DCM groups A (2.60 (1.71–3.58)) and B (2.52 (1.51–3.72)) than in the control group 1.75 (1.28–1.96) mg/L, P<0.001. Neopterin correlated positively with the number of macrophages in biopsy specimens (P<0.05) acute phase proteins: C-reactive proteins (P<0.05); fibrinogen (P<0.01); and NYHA functional class (P<0.05) and negatively with left ventricular ejection fraction (P<0.05). Conclusions. Neopterin but not β-2 microglobulin concentration reflected immune response in biopsy specimens. Neopterin correlated with acute phase proteins and stage of heart failure and may indicate a general immune and inflammatory activation in heart failure.